Characterising risk of non-steroidal anti- inflammatory drug-related acute kidney injury: a retrospective cohort study. Issue 1 (2022) - Lin, Sharon X; Holroyd, Christopher; Johnson, Ruth; Barnes, Nicola; Phillips, Thomas
No abstract available